Performance characteristic of endoscopic ultrasound-guided fine needle aspiration is unaffected by pancreatic mass size - Jayapal Ramesh (Endoscopy International Open, 2016)
Background and study aims: Despite a well-established tool for diagnosis of pancreatic masses, endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) studies have shown suboptimal diagnostic performance at divergent mass sizes. Since the impact of gold standard follow-up and presence of on-site evaluation on this observation is unknown, we aimed to study the performance characteristics of EUS-FNA under these strict conditions. Patients and methods: EUS-FNA results from pancreatic mass lesions performed between July 2000 and March 2013 were evaluated. All patients with histological follow-up were then stratified into four groups: Group A ( ≤ 10 mm), Group B (11 – 20 mm), Group C (21 – 40 mm), and Group D (> 40 mm). Sensitivity and diagnostic accuracy were calculated for each group and compared. Results: A total of 612 /3832 (16 %) patients with pancreatic masses who underwent EUS-FNA had histology confirmation. Of these, 81 were excluded due to unavailable lesion size, while the rest formed the study cohort. Mean age (SD) was 65.8 years (9.3) with 51.2 % female. The mean number of passes for the entire cohort was 2.9 (SD 1.9; range 1 – 12); patients in group D had a significantly higher number of passes for on-site diagnosis (P = 0.0124). There was no significant difference between the groups for sensitivity (P = 0.1134) or diagnostic accuracy (P = 0.2111). Proportional trend analysis revealed no significant correlation between size and sensitivity (P = 0.6192). The size of lesion measured by EUS was not associated with sensitivity or specificity after adjusting for age, sex, and pancreatic location. Conclusion: In the presence of rapid on-site cytopathology and when final histology is taken as the gold standard, pancreatic mass size does not affect the performance characteristics of EUS-FNA.